2022
DOI: 10.1111/ijd.16565
|View full text |Cite
|
Sign up to set email alerts
|

Adalimumab efficacy is inversely correlated with body mass index (BMI) in hidradenitis suppurativa

Abstract: Background Adalimumab is the only FDA‐approved biologic for hidradenitis suppurativa (HS). In the setting of increasing obesity rates worldwide, the relationship between adalimumab efficacy for HS and BMI is essential to understand. We assessed this relationship through markers of disease severity and inflammation. Methods Institutional review board‐approved retrospective chart review of Montefiore/Einstein HS Center (HSC) patients (n = 57) treated with adalimumab. The relationship between BMI and adalimumab e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…Antibiotics have long been a mainstay of HS treatment in early disease 61 . In a recent trial, ertapenem, a potent bactericidal antibiotic was shown to reduce HS inflammatory disease activity as well as reduction of IL‐6 and CRP 62 . Recently published clinical data in HS also demonstrated the clinical benefit of combining rifampicin/clindamycin with adalimumab, 63 as well as alternatively using anti‐biofilm surfactant wound gels during surgery with high clinical response 64 and reductions of inflammatory genes like IL‐17, IL‐6 and IL8.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotics have long been a mainstay of HS treatment in early disease 61 . In a recent trial, ertapenem, a potent bactericidal antibiotic was shown to reduce HS inflammatory disease activity as well as reduction of IL‐6 and CRP 62 . Recently published clinical data in HS also demonstrated the clinical benefit of combining rifampicin/clindamycin with adalimumab, 63 as well as alternatively using anti‐biofilm surfactant wound gels during surgery with high clinical response 64 and reductions of inflammatory genes like IL‐17, IL‐6 and IL8.…”
Section: Discussionmentioning
confidence: 99%
“…Además, la obesidad interfiere negativamente en la efectividad de los nuevos tratamientos para la hidrosadenitis supurativa. Nosrati et al 27 demuestra que los pacientes con un IMC >30 sufren un deterioro físico-clínico a pesar del tratamiento completo con Adalimumab. Teniendo en cuenta lo referido anteriormente, no es de extrañar que las nuevas líneas de investigación reconsideren una terapia basada en el peso para el manejo de esta patología.…”
Section: Discusionunclassified
“…In this issue of JAMA Dermatology , the cohort study by Nosrati et al provides evidence supporting the extension of intravenous ertapenem therapy to an average course duration of 13 weeks for HS recalcitrant to combinations of broad-spectrum oral antibiotics, antiandrogen therapies, and immunomodulating biologics. Although this investigation advances treatment options for the vexing problem of recalcitrant HS, adopting prolonged ertapenem treatment courses comes with substantial individual and public health considerations.…”
mentioning
confidence: 99%
“…The study’s limitations must also be carefully considered when interpreting these findings . The authors used the HS Physician Global Assessment to measure disease improvement; however, the average reduction in score fell short of the accepted clinically meaningful threshold of a 2-point decrease.…”
mentioning
confidence: 99%
See 1 more Smart Citation